Management Strategies for Occupational Health and Safety during Prevention Intervention Development - Ismail, Moamen Abdelfadil; alshahrani, Jawaher said saad; Alghamdi, Ohud Ghulayyim; hamamah, Saeed Yahya saeed al abu; Alotaibi , Muslat Howidi D; ALTAMIMI, WEJDAN ALI BIN AMER; Alotaibi , Mona Mojeb; Alotibi , Amaal Mugeb; ALBUGHULI, HASAN HUSSAIN; narql, Rayan Abdulhamed yuldash; majrashi, Ghaliah abdu ali; AL AMRI, HAMZAH FAHAD; et al. (Journal of Ecohumanism, 2024)
Background: Occupational Health and Safety (OHS) professionals, including managers and advisors, often face exclusion from key organizational decision-making processes, limiting their influence on workplace safety improvements. While prior research highlights the technical aspects of OHS roles, little attention has been given to the strategic approaches professionals use to navigate organizational challenges and influence safety systems effectively. Methods:This study was conducted through in-depth interviews with twelve OHS professionals from public and private sector organizations. Participants, comprising six OHS managers and six OHS advisors, had at least six years of experience. Data collection involved semi-structured and structured interviews, where participants provided insights into their responsibilities, strategic approaches, and organizational positioning. Thematic analysis using NVIVO software categorized strategies based on existing frameworks while identifying new approaches. An impact evaluation framework with seven levels was applied to assess the effectiveness of these strategies. Results: OHS professionals were motivated by personal experiences, a commitment to workplace safety, and the desire to drive organizational change. Their primary responsibilities included advising management, ensuring regulatory compliance, and maintaining OHS management systems. While most professionals operated at both strategic and operational levels, their focus was primarily on organizational and human-centered dimensions rather than technical aspects. Strategic approaches varied, with some relying on traditional compliance-based strategies, while others employed adaptive tactics, such as the “political reflective navigator” model, to influence workplace safety culture. Conclusion: The study highlights the diverse roles and strategies employed by OHS professionals to enhance workplace safety. Despite their marginalization in decision-making, those who adopt flexible, advocacy-driven strategies can exert significant influence on organizational safety practices. Future research should explore additional contextual factors affecting OHS professionals' strategic efficacy, particularly in different industry settings.